Modulatory Effect of the Euro-Lupus Low-Dose Intravenous Cyclophosphamide Regimen on Circulating Immune Cells in Systemic Lupus Erythematosus - Gabcova, Gabriela; Horak, Pavel; Mikulkova, Zuzana; Skacelova, Martina; Zehnalova, Sarka; Smrzova, Andrea; Petrackova, Anna; Mrazek, Frantisek; Kriegova, Eva (Archivum immunologiae et therapiae experimentalis, 2019)
A Euro-Lupus regimen of low-dose intravenous cyclophosphamide (CFA) is commonly used to treat severe organ manifestations of systemic lupus erythematosus (SLE), particularly lupus nephritis (LN). There are no data on the distributions and dynamics of immune cell populations in patients with various treatment outcomes. The circulating immune cells of 11 female SLE patients were assessed before and after Euro-Lupus regimen (cumulative dose of 3000 mg CFA) by flow cytometry together with those of 16 healthy women. A subanalysis was performed in LN patients who achieved complete remission (CR; n = 3), partial remission (PR; n = 4), and no response (NR; n = 2). In SLE, the Euro-Lupus regimen decreased the percentage and absolute count of B cells; increased the percentage of CD8+ T cells, T regulatory cells, neutrophils, and monocyte subsets; and activated T and NK cells compared to healthy controls (P < 0.050). Patients with LN achieving CR had significantly lower proportions of CD27+ B memory cells compared to poor responders (PR/NR, P = 0.035). The post-treatment percentages and absolute numbers of B cells, T cells, NK cells, monocytes, and neutrophils showed high inter-individual variability with no association with treatment outcome. Our pilot study revealed the dynamics of changes in immune cell populations in SLE patients during a Euro-Lupus regimen, mainly the lowering of B cells. In LN patients who achieved CR, a lower proportion of CD27+ B memory cells was evident compared to poor responders (PR/NR). Further studies on usefulness of monitoring immune cells for treatment response prediction on larger cohorts are needed.
Keywords: Flow cytometry; dospělí; systémový lupus erythematodes; Cyclophosphamide; Lupus nephritis; Female; lymfocyty; Administration, Intravenous; průtoková cytometrie; Adult; ženské pohlaví; mladý dospělý; intravenózní podání; lidé; Immunosuppressive Agents; Flow Cytometry; Immunomodulation; Treatment outcome; Immunophenotyping; kohortové studie; Lupus Erythematosus, Systemic; Middle Aged; Cohort Studies; Remission Induction; Lupus Nephritis; nefritida při lupus erythematodes; indukce remise; Young Adult; krevní oběh; Lymphocytes; Blood Circulation; imunologická paměť; lidé středního věku; SLE; imunomodulace; cyklofosfamid; Clinical Protocols; imunosupresiva; klinické protokoly; Immunologic Memory; Humans